Study Family Cohesion Prediction Model Based on Differentiation and Attitude to Love: The Mediating Role of Marital Intimacy in Married Women - Mokhtari, Zahra; Mardani, Zahra (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The aim of the present research is to examine the predictive model of family cohesion based on differentiation and attitude towards love: the mediating role of marital intimacy in married women. Method: The research is descriptive-correlational, employing structural equation modeling. The study population consisted of all married women in the city of Isfahan who had been married for at least three years and were currently living with their spouses. A total of 225 individuals were selected as the sample using voluntary sampling. The data collection tools included the Fisher Family Cohesion Scale (Fisher et al., 1992), the Skowron and Smith Self-Differentiation Questionnaire (2003), the Hendrix and Hendrix Love Attitude Scale (1997), and the Thompson and Walker Marital Intimacy Questionnaire (1983), all of which have been validated. To achieve the objectives of the present research, initially, a descriptive analysis of the data obtained from the questionnaires was conducted. Subsequently, structural equation modeling (SEM) was used to reduce the independent variables. Results: The results of the data analysis indicated that the second to fifth hypotheses of the research regarding the relationships between the study variables were confirmed. Based on these relationships, in total, 88% of the variations in the dependent variable (family cohesion) were predicted by the variables of the final model. Conclusion: Furthermore, according to the final model obtained from structural equation modeling, the independent variables of attitude towards love, marital intimacy, and differentiation had a direct impact on the family cohesion of married women.